The in-ear region as a novel anatomical site for ecg signal detection: validation study on patients affected by atrial tachyarrhythmias. (19th May 2022) - De Lucia, R; Zucchelli, G; Della Volpe, S; Fiorentini, F; Parollo, M; Giannotti Santoro, M; Barletta, V; Canu, A; Mazzocchetti, L; Bongiorni, MG
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose: Early detection of cardiac arrhythmias is a major opportunity for mobile health, as portable devices nowadays available can detect multiple-lead electrocardiogram (ECG). The study aims to validate the in-ear region as a new anatomical site for ECG signal detection in patients (pts) affected by atrial tachyarrhythmias. Methods: We performed the ECG using KardiaMobile 6L device on 20 patients affected by tachyarrhythmias and admitted to our hospital for electrical cardioversion. All the digital ECGs were detected in a modified modality or using the left in-ear region instead of the right hand. All the recorded ECGs were analyzed by the device and the results checked by two cardiologists. Results: We successfully collected all 20 modified digital ECGs performed on the group of 20 pts (age 68.4 ± 9.2 years; male 60%; 14pts in atrial fibrillation (AF); 6pts in atrial flutter (AFl); medium HR 94±28.4bpm; 65% affected by hypertension; 5% affected by diabetes mellitus; 95% in NOACs). In case of AF, the KardiaMobile 6L diagnosis of the ECG detected by this modified modality was correct in 100% of cases. In the 6 pts affected by AFl the KardiaMobile 6L diagnosis was "normal" in 3 cases and "not classified" in the other 3. For that reason, in these 6 pts, we performed a new digital ECG using the KardiaMobile 6L in the standard modality, and the diagnosis for each patients was the same. Conclusion: The in-ear region could be a reliable novel anatomical site for ECG signal detection in patients affected by atrial fibrillation. Further studies are needed to overcome the misdiagnosis of digital ECG in case of patients affected by atrial flutter. These data support the development of new portable ECG devices using the left in ear region and so leaving at least one hand free.